Climate-smart agriculture in Khyber Pakhtunkhwa, Pakistan - Miller, Vail; Giles, James; Khan, Muhammad; Mumtaz, Hira; Savelli, Adam; Grosjean, Godefroy (Bioversity International and the International Center for Tropical Agriculture, 2021)
The Climate-Smart Agriculture Profile for Khyber Pakhtunkhwa, Pakistan, provides an overview of the agriculture sector in the Province along with the major climatic and non-climatic challenges impacting its development. Climate projections are used to support an assessment of future hazards likely to impact crop and livestock production. The profile then assesses the most promising Climate-Smart Agriculture (CSA) practices and technologies for 10 key commodities in the province, along with their impact on a range of indicators related to increased productivity, enhanced resilience, and a reduction in greenhouse gas (GHG) emissions. Finally, the text provides snapshots of the enabling policy and institutional context and the potential financing sources for greater uptake of CSA in Khyber Pakhtunkhwa.